(3SdhGf GdeWGY aj YOhGf GdCJHGYs - (3eMeO Hf CHj GdbGSe Hf Ydj GdbQTj Gdecj MLI GdOjf GdfMhj, GHf GdeXaQ,J (B568 (3g` s
(3ChdgG (B:s
(3hHYO aEf eeG CaVi Hg Edjg EVWQGQ GdEZJQGH hCJjGH GdEcJFGH Cf CXaQ aj Gddg JYGdi hdg GdMeO HehGNGJ ebjd YKQGJ GdSGOGJ s
(3BNQgG (B:s
(3heG JTGDhf EdG Cf jTGA oebdH GdbdhH hGdCHUGQ hoeWdY GdZjhH hGdCSQGQ Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3fSNI ChdjZes
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B998s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs